Exploring the dual character of metformin in Alzheimer's disease. (1st April 2022) - Ning, Pingping; Luo, Anling; Mu, Xin; Xu, Yanming; Li, Tian
Abstract: Alzheimer's disease (AD) is the most common neurodegenerative disease, which results in dementia typically in the elderly. The disease is mainly characterized by the deposition of amyloid beta (A β ) plaques and neurofibrillary tangles (NFTs) in the brain. However, only few drugs are available for AD because of its unknown pathological mechanism which limits the development of new drugs. Therefore, it is urgent to identify potential therapeutic strategies for AD. Moreover, research have showed that there is a significant association between Type 2 diabetes mellites (T2DM) and AD, suggesting that the two diseases may share common pathophysiological mechanisms. Such mechanisms include impaired insulin signaling, altered glucose metabolism, inflammation, oxidative stress, and premature aging, which strongly affect cognitive function and increased risk of dementia. Consequently, as a widely used drug for T2DM, metformin also has therapeutic potential for AD in vivo . It has been confirmed that metformin is beneficial on the brain of AD animal models. The mechanisms underlying the effects of metformin in Alzheimer's disease are complex and multifaceted. Metformin may work through mechanisms involving homeostasis of glucose metabolism, decrease of amyloid plaque deposition, normalization of tau protein phosphorylation and enhancement of autophagy. However, in clinical trials, metformin had little effects on patients with mild cognitive impairment or mild AD. Pathological effects and negative clinical results of metformin on AD make the current topic quite controversial. By reviewing the latest progress of related research, this paper summarizes the possible role of metformin in AD. The purpose of this study is not only to determine the potential treatment of AD, but also other related neurodegenerative diseases. Highlights: ∙ Clarify the mechanisms by which metformin may be neuroprotective role in animal model of AD ∙Summarize the correlation between metformin treatment and AD risk ∙It is controversial whether metformin treatment can reduce the risk of AD or other neurodegenerative diseases.